A review of polygeneration systems with CO2 working fluid. (1st September 2022) - Bellos, Evangelos; Said, Zafar; Lykas, Panagiotis; Tzivanidis, Christos
Highlights: A review of polygeneration with CO2 working fluid is conducted. The challenges and the future trends in the field are presented in detail. High energy and exergy efficiencies are reported for many CO2 polygeneration units. Exergy efficiencies up to 70% are reported; something that indicates sustainability. Viable systems are reported with a payback period of 3–4 years. Abstract: CO2 is a promising working fluid which gains more and more attention in the last years in the energy sector and especially in polygeneration which is a promising application for efficient and cost-effective energy production. The objective of the present study is to perform a comprehensive review and discussion of the studies that investigate the concept of polygeneration with CO2 thermodynamic cycles; something that is missing from the existing literature. More specifically, the analysis focuses on the plants that exploit renewable energy sources, such as solar energy, geothermal energy or biomass, and waste heat, as well as this work includes the systems driven by fossil fuels. The energetic, exergetic, and financial indexes of the examined configurations are summarized and discussed. Furthermore, it is important to say that the reviewed systems contain different prime movers, such as the CO2 Brayton cycle, various secondary devices, and different useful outputs (e.g. heating, cooling, electricity). According to the reported data, the energy efficiency of the polygeneration systems can be over 100 %, the exergy efficiency up to 70 %, and the payback period of various designs is around 3–4 years. The challenges of these plants and the future trends in the field are discussed in the present review investigation. Finally, it is crucial to state that the included studies are classified according to the kind of energy source and the emphasis is given in the report on the systems' thermodynamic efficiencies.